Computational insights into flavonoids inhibition of dengue virus envelope protein: ADMET profiling, molecular docking, dynamics, PCA, and end-state free energy calculations - Amar Waiba; Anuraj Phunyal; Tika Ram Lamichhane; Madhav Prasad Ghimire; Hari Nyaupane; Ashish Phuyal; Achyut Adhikari (PLoS ONE, 2025)
Dengue virus is a critical worldwide health concern, and efforts to identify useful antiviral drugs remain imperative. This study utilized computational techniques to investigate the flavonoids as a potential inhibitor of the dengue virus envelope protein (PDB ID: 1OKE). 33 flavonoids were docked among them, 5-hydroxy-3-(4-hydroxyphenyl)-7-[(2S, 3R, 4S, 5S, 6R)-3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]oxychromen-4-one (FLA1) showed the best binding affinity of ˗9.1 kcal/mol towards the E protein. Molecular dynamics simulations (100 ns) were carried out to analyze the stability and interaction of protein-ligand complexes, including parameters such as RMSD (FLA1 of 2.36 ± 0.43 Å), RMSF, Rg, SASA, hydrogen bonding, and RDF. In addition, PCA and DCCM analysis exposed considerable conformational differences and residue correlations favoring FLA1 stability. The binding free energy calculations using the MM/PBSA methodology confirmed the strong binding (˗29.1 ± 5.83 kcal/mol) of FLA1 to the target protein. ADMET profiling also revealed good pharmacokinetic properties. These findings suggest FLA1 is a possible inhibitor of the dengue virus and a promising drug candidate for the development of antiviral drugs in the future.